Lipid metabolism in in vitro produced embryos and epiblast-derived stem cells - Guven Ates, Gizem (2023)
Infertility is a disease of the reproductive system defined as the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse (PierreZegers-Hochschild et al., 2009). Between 9-15% couples will have infertility problems during their lifetimes and for these infertile people, the percentage searching for medical assistance is around 56% in more developed countries and 51% in less developed countries (Boivin et al., 2007). To treat infertility, Assisted Reproductive Technologies (ARTs) were developed beginning with artificial insemination (Jouannet, 2009). Today, ART also consists of in-vitro fertilization (IVF), intracytoplasmic sperm injection and cryopreservation of germ cells (i.e., sperm, oocyte and embryos) (Sejbaek et al., 2013).